The effect of voids on the quasi-static tensile properties of carbon fiber/polymer-laminated composites. (June 2018) - Liu, Haolong; Cui, Haitao; Wen, Weidong; Su, Xuming; Kang, Hongtae; Engler-Pinto, Carlos
Static longitudinal/transverse tensile tests for unidirectional carbon fiber/polymer (T300/924) laminates and laminates with lay-ups[ 0 / ± 45 / 0 / 90 ] s at various void levels were conducted, and degradations in stiffness/strength were observed with the presence of voids. The void levels were controlled by compression pressure during the compression molding process. The characterization of voids was achieved by digital microscopy image analysis; the density distributions of equivalent diameters and aspect ratios were analyzed with respect to compression pressure. For the purpose of quantifying the effect of voids on the static mechanical properties of composites, a stiffness prediction method based on the Mori-Tanaka method and void geometric statistical data have been used with the implementation of a finite element model of the representative volume element for unidirectional composites; the prediction results show good correlation with experimental data. Finally, a modified continuum damage model for laminated composites with the presence of voids was proposed, the model is capable of capturing the effect of voids; and gradual damage analysis for carbon fiber/polymer composite laminates at different void levels was conducted to evaluate the effect of voids on their tensile properties.